Partial thyroidectomy for papillary thyroid microcarcinoma: Is completion total thyroidectomy indicated?. (May 2017) - Dobrinja, C.; Pastoricchio, M.; Troian, M.; Da Canal, F.; Bernardi, S.; Fabris, B.; de Manzini, N.
Abstract: Aim: Papillary thyroid microcarcinoma (PTMC) is increasing in incidence. Despite its excellent clinical outcomes, there is still debate regarding which surgical approach is more appropriate for PTMC, procedures including hemithyroidectomy (HT), total thyroidectomy (TT), and completion thyroidectomy (CT) after initial HT and histopathologic examination confirming a PTMC. Here we report our experience in the surgical management of PTMC. Methods: We conducted a retrospective evaluation of all patients who received a postoperative diagnosis of PTMC between January 2001 and January 2016. Every patient was divided according to the type of surgery performed (TT or HT alone). Follow-up consisted of regular clinical and neck ultrasonographic examination. Clinical and histopathological parameters (e.g. age, sex, lesion size, histological features, multifocality, lymph node metastases, BRAF status when available) as well as clinical outcomes (e.g. complications rates, recurrence, overall survival) were analyzed. Results: Group A consisted of 86 patients who underwent TT, whereas Group encompassed 19 patients who underwent HT. Mean follow-up period was 58.5 months. In Group A, one patient (1.2%) experienced recurrence in cervical lymph nodes with need for reoperation. In Group B, eight patients (42%) underwent completion thyroidectomy after histopathological examination confirming PTMC, while one patient (5.3%) developed PTMC in the contralateral lobe with need for reoperation at 2 years after initial surgery. Multifocality was found in 19 patients in Group A (22%). Of these, 14 presented bilobar involvement, whereas in 3 cases multifocality involved only one lobe. 1 patient in Group B (5.3%) presented with unilateral multifocal PTMC ( p = 0.11). Conclusions: Low-risk patients with PTMC may benefit from a more conservative treatment, e.g. HT followed by close follow-up. However, appropriate selection of patients based on risk stratification is the key to differentiate therapy options and gain better results. Highlights: The best surgical approach for PTMC is still object of debate. Hemithyroidectomy may be adequate for low-risk patients, with no need for routine completion thyroidectomy. Total thyroidectomy or completion thyroidectomy is rather indicated in selected patients with risk factors for mortality and recurrence. Accurate patient selection is important to achieve the best results.